Essential Oils of Foeniculum vulgare subsp. piperitum and Their in Vitro Anti‐Arthritic Potential. Issue 11 (16th October 2020) - Marrelli, Mariangela; Amodeo, Valentina; Viscardi, Florinda; De Luca, Michele; Statti, Giancarlo; Conforti, Filomena
Abstract: Wild Foeniculum vulgare subsp. piperitum (C.Presl) Bég. flowers, fruits and leaves were extracted with steam distillation and obtained essential oils (EOs) were characterized using GC/MS. The study was designed to verify the potential effectiveness of fennel EOs in the treatment of inflammation and arthritis. Since tissue proteins denaturation is a major cause of arthritic diseases, fennel EOs and their main constituents were evaluated for their ability to inhibit the heat‐induced proteins degradation using bovine serum albumin as a protein model. Moreover, the in vitro inhibitory effects of the three EOs on the pro‐inflammatory mediator nitric oxide (NO) production were verified in LPS‐stimulated RAW 264.7 cells. Estragole (28.81–33.40 %), anethole (24.16–27.40 %), fenchone (9.76–18.48 %), α ‐phellandrene (1.63–8.37 %) and limonene (5.54–6.05 %) were the major constituents. All the EOs showed a concentration‐dependent biological activity, being the flower EO the most effective in inhibiting NO production (IC50 =232.2±11.3 μg/mL). The leaf EO showed a very good bovine serum albumin (BSA) anti‐denaturation activity (IC50 =95.9±2.4 μg/mL). Moreover, four components were proved to be effective in protecting protein from heat‐induced degradation, being α ‐phellandrene the most active compound (IC50 =73.2±1.9 μg/mL). Abstract :